A comparison of the allometric growth in Uca leptodactyla (Crustacea : Brachyura : Ocypodidae) from two subtropical estuaries - Cardoso, RCF; Negreiros-Fransozo, M. L. (Cambridge University Press, 2004)
The allometric growth of Uca leptodacyla from two distinct subtropical estuaries on the Brazilian coast was evaluated concerning its growth pattern and size at onset of sexual maturity. Females attained maturity at similar sizes in both sites (4.1 mm of carapace length in Indaia and 4.2 mm in Ubatumirim), while males differed slightly. They reached the size at sexual maturity of 5.3 mm of carapace length in Indaia and 4.6 mm in Ubatumirim. Growth pattern is Usually similar among crabs from distinct Sites while size at sexual maturity is frequently different. However, in the case of U. leptodacyla it did not occur, probably due to the strong habitat similarity and intrinsic features of this species.